2021
DOI: 10.3390/a14050157
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Delay Multiply and Sum Algorithm for Microwave Medical Imaging Using Spark Big Data Framework

Abstract: Microwave imaging systems are currently being investigated for breast cancer, brain stroke and neurodegenerative disease detection due to their low cost, portable and wearable nature. At present, commonly used radar-based algorithms for microwave imaging are based on the delay and sum algorithm. These algorithms use ultra-wideband signals to reconstruct a 2D image of the targeted object or region. Delay multiply and sum is an extended version of the delay and sum algorithm. However, it is computationally expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…For example, the computation time is of paramount importance in the case of stroke detection as the patient seeks urgent help. Various algorithms are used to improve computational efficiency, such as hardware resources, including graphical processing units, field-programmable gate arrays [26] and software frameworks such as Spark and Hadoop [27]. For applications like AD monitoring, the computation time becomes less important than accuracy.…”
Section: Discussion and Comparisonmentioning
confidence: 99%
“…For example, the computation time is of paramount importance in the case of stroke detection as the patient seeks urgent help. Various algorithms are used to improve computational efficiency, such as hardware resources, including graphical processing units, field-programmable gate arrays [26] and software frameworks such as Spark and Hadoop [27]. For applications like AD monitoring, the computation time becomes less important than accuracy.…”
Section: Discussion and Comparisonmentioning
confidence: 99%
“…Future work will be done to optimize it further to obtain the exact dimension of the malignant target. The image quality and contrast can also be improved through delay and sum (DAS) [35], [36], delay multiply and sum (DMAS) [37]- [39] and channel-ranked delay and sum (CR-DAS) [40], [41] algorithms.…”
Section: Imaging Of Stroke and Brain Atrophymentioning
confidence: 99%
“…This data can be used to compare the diagnosis of the target patient and accurately reconcile the results. Recent research has been focused on utilizing a deep learning network [198], PySpark-based reconstruction [199] and parallel delay multiply and sum image reconstruction algorithm [200], which performed more efficiently than the delay multiple and sum algorithm. The experimental results from these researches have shown that the Spark significantly accelerates the imaging reconstruction process without affecting the accuracy.…”
Section: Machine Learning Based Microwave Sensing and Imaging Algorithmsmentioning
confidence: 99%